Germplasm rescue and repatriation - Joshi, Bal Krishna; Ghimire, Krishna Hari; Gurung, Rita; Gauchan, Devendra (NAGRC, 2020)
Due to many factors such as increase access and availability of modern varieties, change in market preferences, low productivity of native landraces and climate change, crop landraces are threatened and are at the risk of losing from the fields. Still there are many rare and unique landraces conserved by farmers in different parts of the country. Native agricultural genetic resources that are being grown in red zone areas are all endangered. Unique and rare landraces as well as landraces grown in small areas by few farmers are also endangered. Different natural calamities also make native landraces endangered. Such landraces are lost if further conservation action did not take place. Exploration and collection of such endangered landraces is called germplasm rescue. National gene bank started rescue since 2014 for buckwheat diversity in Dolpa district.